Focal mechanism of the great 2004 Sumatra earthquake by joint inversion of GPS deformation field and GRACE gravity change - Habibi, Hamid; Raoofian-Naeeni, Mehdi (Journal of geodynamics, 2020)
In this study, the gravity changes observed by GRACE satellites along with the deformation field determined from GPS velocity vectors are used to estimate the fault parameters of 2004 Sumatra-Andaman Earthquake (SAE) by the inversion of PSGRN/PSCMP dislocation model. To do so, the co-seismic gravity changes are determined by fitting a time-series function to the GRACE monthly gravity fields and the effects of hydrology are suppressed with the aid of Global Land Data Assimilation (GLDAS) model. To increase the accuracy of inversion process, the GPS observed co-seismic and post-seismic displacements from 90 stations scattered across the deformed area are also used to constrain the inversion algorithm. The inversion is performed via the Particle Swarm Optimization (PSO) method that minimizes the error between the model-predicted and observed deformation and gravity changes. To this end, the PSGRN/PSMCP dislocation model predicts the deformation and gravity changes for each candidate fault in the PSO iterative process. It is shown that the joint use of the GPS and GRACE data in determination of focal mechanism, results in a fault model that is better consistent with the geometry of the existing subduction zone compared to the inverted fault using only GPS or GRACE data. Due to the complex geometry of the Sunda Trench, a discretized rectangular fault system is considered that allows the depth, slip, strike angle and dip angle vary between the sub-faults. In fact, the estimated fault model consists of 100 sub-faults with a total moment magnitude of Mw = 9.23 that matches the curved geometry of the Sunda Trench. The fault model reveals that the slip has a greater magnitude in segments near the northern Sumatra and Nicobar islands while for the segments of the fault, near the Andaman Islands, the slip is relatively smaller and has its greater magnitudes at depth. The depths and dip angles of the estimated fault model are compared to the SLAB2 3D geometry provided for the Sumatra and Java subduction zones and through this comparison, the RMSEs of 6.0 km for the depth and 3.1 ° for the dip angle are obtained.